2015
DOI: 10.1039/c4ay02374a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of eight isoflavones in Radix Puerariae by capillary zone electrophoresis with an ionic liquid as an additive

Abstract: Isoflavones are the main active components in Radix Puerariae, the dry root of Pueraria lobata or P. thomsonii. We developed a simple capillary zone electrophoresis (CZE) method with an ionic liquid (IL) as an additive for the simultaneous determination of eight isoflavonesononin, daidzin, genistin, biochanin A, formononetin, puerarin, genistein and daizeinin Radix Puerariae. The experimental conditions, including the concentration of sodium tetraborate, the pH, the type and concentration of the ILs, the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Radix Puerariae, the dry root of Pueraria lobata, also contains large amounts of isoflavones, including puerarin, daidzin, genistein, and biochanin A. These samples are generally extracted with pure methanol and subjected to an ultrasonic bath for 30 min (Niu and others ; Xiao and others , ).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Radix Puerariae, the dry root of Pueraria lobata, also contains large amounts of isoflavones, including puerarin, daidzin, genistein, and biochanin A. These samples are generally extracted with pure methanol and subjected to an ultrasonic bath for 30 min (Niu and others ; Xiao and others , ).…”
Section: Sample Preparationmentioning
confidence: 99%
“…With the commonly used separation buffers, formononetin and biochanin A, which have very similar chemical structures, could not be separated. Xiao and others () have investigated the use of ionic liquids as additives to improve separation of these isoflavones. They found that the addition of ILs had little effect on the EOF, suggesting that the separation mechanism is most likely to be either hydrophobic interactions between the analytes and the ILs and/or the formation of complexes between the analytes and the IL.…”
Section: Separation and Detection Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…HP‐β‐CD was also used to improve the separation of diastereomeric pairs, the separation of catechin, epicatechin, cinchonains Ia, Ib, IIa, and IIb from Trichilia catigua samples on the same run could be realized in less than 12 min by using voltage reduction . In our previous study, a simple CZE method with an IL, BMImBF 4 as an additive was developed for the simultaneous determination of eight isoflavones including ononin, daidzin, genistin, biochanin A, formononetin, puerarin, genistein and daizein in Radix Puerariae . The eight analytes (detection wavelength 260 nm) were well separated within 9 min after systematic optimization of the parameters.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Ohwi or P. thomsonii Benth, contains large amounts of isoflavones. A CZE method with an IL 1‐butyl‐3‐methylimidazolium tetrafluoroborate as additive for the simultaneous determination of eight isoflavones in Radix Puerariae . The results indicated that P. lobata contains more isoflavones than P. thomsonii .…”
Section: Applicationsmentioning
confidence: 99%